Desmitificando a Discalculia a partir de vivências escolares: narrativas de alunos, mães e professora do Grupo de Atendimento Psicopedagógico - LARA FERNANDA LEONEL RAMIRES (2025)
In this study, we will address Dyscalculia, which has pedagogical implications for learning mathematics. Dyscalculia is multifaceted; therefore, our general objective is to investigate the identification processes and experiences in the schooling process of students with Dyscalculia. Given this, we chose to conduct a qualitative research methodology, which allowed us to carry out semi-structured interviews, fully transcribe them, and transform them into narratives. These steps were conducted with seven participants: three mothers, three students, and the teacher from the Educational Support Group (GAPSI). Subsequently, excerpts were selected and analyzed using the Thematic Analysis method. Based on the selected excerpts, we found it necessary to address the Historical-Cultural Theory, Federal Law No. 14.254/2021, SEMED Resolution No. 227/2021, GAPSI, and a review of dissertations and theses on Dyscalculia in Mathematics Education or Mathematics Teaching. The study investigated how the identification and schooling process of students with Dyscalculia took place, showing that the identification process occurred alongside schooling, with support from GAPSI and the Municipal Department of Education. Additionally, the need for continuous support, pedagogical adaptations, and awareness-raising efforts was observed to reduce prejudice and promote inclusion. To achieve this, collaboration between family, school, and professionals is essential to ensure rights and effective learning strategies. The narratives revealed school trajectories marked by exclusion due to a lack of knowledge, as many schools still operate based on the notion of normality. As a consequence of this structure and the lack of awareness about the condition, initially, individuals with Dyscalculia were perceived as lazy by their mothers and faced prejudice both within their families and in school settings. However, after identifying the reasons behind their discouragement and difficulties in Mathematics, the mothers experienced feelings of guilt for their previous judgments but became actively involved in following the steps guided by the psychopedagogue.